SHIPMAI: Secure and HIgh Performance Mobile Agent Infrastructure. - Tkito, Reda. (University of Ottawa (Canada), 2001)
In the computer area, the term "agent" describes a software entity that performs tasks on behalf of the user. Recently, the mobile agent technology has become an attracting research subject, especially in the field of Distributed Object Technology (DOT), where it is believed that this new paradigm could considerably rectify the shortcomings of its predecessors. As a relatively new concept, the agent technology is still immature, although it is gathering its share of investment money. In our opinion, a major problem still limiting widespread use of mobile agents is the lack for an appropriate supporting platform. The existing agent infrastructures consider differently the issues related to the paradigm; and none comes with a design that appropriately addresses all of them; security being the most poorly treated aspect. This thesis presents our Java-based mobile agent platform called SHIPMAI. The proposed platform aims to efficiently provide all necessary agent services, namely, execution, security, transport, tracking, communication, and persistence. Those MA services are reasonably distributed thanks to the smart agent-space hierarchy introduced by SHIPMAI. Our system architecture consists of private agent domains managed by ADCs (Agent Domain Controllers). Each domain contains several AEEs (Agent Execution Environments), which are destined to host agents. The idea is partially inspired from the Intranet concept. To improve the system flexibility, policies are integrated so as to leverage the functioning of SHIPMAI and to control the behavior of agents. The thesis work includes also the development, on top of SHIPMAI, of a "Mobile Agent-Based Software Distribution" application. MABSD uses agents in order to provide a highly automated delivery and installation of software packages.
Keywords: Engineering, Electronics and Electrical.